2014
DOI: 10.1159/000360841
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia in Very Preterm Children: A Review of the Evidence

Abstract: Introduction: Intubation is a known risk factor for dysphonia yet is essential in the perinatal care of many very preterm infants. Children born preterm, who are frequently resuscitated with endotracheal intubation, may be at risk of dysphonia at school age and beyond. Objectives: To identify and describe the evidence pertaining to long-term voice outcomes and risk factors for developing dysphonia in preterm children. Results: In addition to case studies and series, three larger-scale studies have reported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…They consistently present with poorer language than their term-born peers, 3 and may also experience difficulties with voice and speech sound production. 4,5 However, to date, research has not reflected a complete picture of communication ability in children born preterm. Reports have typically focused on isolated domains of communication such as receptive vocabulary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They consistently present with poorer language than their term-born peers, 3 and may also experience difficulties with voice and speech sound production. 4,5 However, to date, research has not reflected a complete picture of communication ability in children born preterm. Reports have typically focused on isolated domains of communication such as receptive vocabulary.…”
mentioning
confidence: 99%
“…Likewise, voice has been infrequently studied among children born preterm, with a 2014 review identifying the need for further research with a particular focus on significant risk factors. 4 Current studies of voice are indicated, especially given the evolution of respiratory management in infants born preterm, and the fact that intubation has been highlighted as a predictor of voice outcomes. 4,10 Given that children born preterm appear to have a heightened risk of language, speech, and voice difficulties, establishing relevant predictors is paramount.…”
mentioning
confidence: 99%
“…Another potentially underestimated complication of PDA surgery is injury to the recurrent laryngeal nerve. This condition may result in voicing disorders and impediments to gas flow in the proximal airways with possible persistence of symptoms into adulthood [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Infants and children who are born very preterm, particularly those who are complicated by major perinatal problems, are often associated with variable degrees of brain injury and adverse neurodevelopmental outcomes [1,2,3,4]. Infants born very preterm are also prone to developing auditory dysfunction and neuropathy [5].…”
Section: Introductionmentioning
confidence: 99%